PENGARUH PEMBERIAN INSENTIF, FASILITAS KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI INSPEKTORAT DAERAH KABUPATEN LABUHANBATU - Zenni Monalista; Sigit Hadiyuwono; Rahmad Diyansyah; Indera Agusman Masyhur Sinaga; Elpi Rozauna Siregar (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
The purpose of this research is to determine the effect of providing incentives, work facilities and motivation partially and simultaneously on the work effectiveness of employees at the Regional Inspectorate of Labuhanbatu Regency. Purpose of the study: To determine the effect of providing incentives, work facilities and motivation partially and simultaneously on the work effectiveness of employees at the Regional Inspectorate of Labuhanbatu Regency. The proposed hypothesis is: There is a significant effect of providing incentives, work facilities and motivation partially and jointly on the work effectiveness of employees at the Regional Inspectorate of Labuhanbatu Regency. The research was conducted at the Regional Inspectorate of Labuhanbatu Regency Jalan H. Idris No. 3 Rantau Prapat, Labuhanbatu Regency, with a population of 62 people, and a sample of 62 people. Based on the analysis results obtained incentives giving have a positive and significant effect on the effectiveness of employees work of the Inspektorat Daerah Kabupaten Labuhanbatu, this is supported by the results of t count analysis t-table (2,774 2,002) at n = 62 at 95% significance level. Work facilities style has a positif and significant effect on the effectiveness of employees work of the Inspektorat Daerah Kabupaten Labuhanbatu, this is supported by an analysis of t count t-table (3,807 2,002) at n = 62 at 95% significance level. Motivation has a not effect on the effectiveness of employees work of the Inspektorat Daerah Kabupaten Labuhanbatu, this is supported by an analysis of t count t-table (2,385 2,002) at n = 62 with a significant level of 95%.Value of F-count F table (23,399 2,79) This states that together (multiple) there are positive and significant effects of incentives giving, work facilities style and motivation on the effectiveness of employees work of employees of the Inspektorat Daerah Kabupaten Labuhanbatu. Thus the hypothesis proposed is accepted by the truth.Â